2016
DOI: 10.1016/j.jsbmb.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

The vitamin D receptor functions as a transcription regulator in the absence of 1,25-dihydroxyvitamin D3

Abstract: The vitamin D receptor (VDR) is a critical mediator of the biological actions of 1,25-dihydroxyvitamin D3 (1,25(OH)2D3). As a nuclear receptor, ligand activation of the VDR leads to the protein’s binding to specific sites on the genome that results in the modulation of target gene expression. The VDR is also known to play a role in the hair cycle, an action that appears to be 1,25(OH)2D3-independent. Indeed, in the absence of VDR as in hereditary 1,25-dihydroxyvitamin D resistant rickets (HVDRR) both skin defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
(49 reference statements)
3
22
1
Order By: Relevance
“…We also observed that ≥20 years of ever in life smoking combined with certain genetic traits, specifically, with bb, Bb+bb (b allele carriers), Ff, and Ff+ff (f allele carriers) are associated with significant crude ORs ranging from 4 to 9 for MetM cases vs healthy controls. Thus, smoke effects in melanoma can be modulated by VDR activity and by the pleiotropic vitamin D endocrine system 11 - 13 , 44 . Further studies are necessary to substantiate this significant and complex issue 10 , 11 , 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that ≥20 years of ever in life smoking combined with certain genetic traits, specifically, with bb, Bb+bb (b allele carriers), Ff, and Ff+ff (f allele carriers) are associated with significant crude ORs ranging from 4 to 9 for MetM cases vs healthy controls. Thus, smoke effects in melanoma can be modulated by VDR activity and by the pleiotropic vitamin D endocrine system 11 - 13 , 44 . Further studies are necessary to substantiate this significant and complex issue 10 , 11 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, smoke effects in melanoma can be modulated by VDR activity and by the pleiotropic vitamin D endocrine system 11 - 13 , 44 . Further studies are necessary to substantiate this significant and complex issue 10 , 11 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…VDR is central to this pathway and is a critical mediator of the biological actions of 1,25-dihydroxy vitamin D, the active form of the hormone. 24 Another important issue is that mean 25(OH)D was <20 ng/mL and similar in both groups. The vast majority of the participants lived in the same geographic area and the blood samples were taken in the same season.…”
Section: Discussionmentioning
confidence: 96%
“…This is because the vitamin D hormone pathway modulates immune function and is important in autoimmune diseases. VDR is central to this pathway and is a critical mediator of the biological actions of 1,25‐dihydroxy vitamin D, the active form of the hormone …”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of VDR action relative to coregulatory factors requires further exploration, including how coregulatory factors are recruited and how their properties are exploited to modulate transcriptional output. Some evidence has emerged that the VDR may function in a ligand-independent manner (i.e., hair follicle cycling) (39,95,(111)(112)(113); however, since VDR/DNA binding is largely ligand dependent both in vitro and in vivo, only a small subset of genes are likely to represent direct targets of this activity (49). It is also unclear how the numerous epigenetic modifications that have been identified across the genome and that are influenced by transcription factors such as the VDR influence genetic output (114).…”
Section: Deficits and Future Directionsmentioning
confidence: 99%